KOMIK SEBAGAI MEDIA PEMBELAJARAN STATISTIKA - Edwin Adrianta Surijah; I Made Feby Anggara; Kadek Indah Yanti; Ni Luh Wahyu Santika Sari; Listiyani Dewi Hartika; Ni Putu Rizky Eka Ramayanti; Komang Ayu Asteria Asawisti Sukma Sugiri (Departemen Psikologi Universitas Pendidikan Indonesia, 2018)
Statistics as a tool in Psychology often being considered as difficult by students. This research aimed to examine effectiveness of comic as learning tool to improve Statistics achievement. Participants of this research were thirty undergraduate students and divided into three groups, Experiment (receive Statistics comic as treatment), Control (no treatment), and Comparison (receive conventional material). The effectiveness of comic were showed in changes in Statistics achievement test results (between group experimental design). The result showed significant changes on each group before and after learning. Experiment Group exhibited most impactful change that evidenced can improve students’ achievement in Statistics.